Python deep learning cookbook : over 75 practical recipes on neural network modeling, reinforcement learning, and transfer learning using Python /: over 75 practical recipes on neural network modeling, reinforcement learning, and transfer learning using Python. (2017) - Bakker, Indra den
No abstract available